Sumber Daya Alam Dalam Pembangunan Berkelanjutan Perspektif Islam - Qur'an, Amanah Aida (Fakultas Ekonomi dan Bisnis Islam (FEBI), Institut Agama Islam Negeri (IAIN) Purwokerto, 2017)
Abstrak Natural resources are a gift given by God almighty to mankind which is khalifa fil ard, but instead humanity is who makes the destruction of nature. Sustainable development is a pattern of development that takes into account the natural balance. Islam gives freedom to utilize the abundant natural resources, especially in Indonesia but there are limitations, also should pay attention to the balance of nature so that natural resources will still be maintained continuity. This study is used the library research. In this study will discuss the concept of natural resources in asustainable development perspective of Islam. Keyword: Natural Resources, sustainable development, Islam.